Optimizing the Patrol of the Sabhara Unit in Preventing the Crime of Theft in Central Lampung Regency - I Ketut Yulio Saputra (Police Studies Review, 2021)
The focus of research in this thesis is the optimization of Sabhara patrol to prevent motor vehicle theft in Central Lampung Regency. The focus of this study is considered important because motor vehicle theft is the highest crime incidence in Central Lampung. Research problems based on the focus of this thesis, namely: (1)How is the implementation Sabhara patrol of Central Lampung Police to preventing motor vehicle theft?; (2)What are the factors that influence the optimize of the Sabhara Unit patrols to prevent motor vehicle theft?; and (3) What are the efforts to increase the optimization of the Sabhara Unit patrols in preventing motor vehicle theft?. This research uses a qualitative approach with the type of research that is the case study. Sources in data collection in the form of primary data sources, secondary data sources, and tertiary data sources, with the techniques of observation, interviews, and document studies. The theories and concepts used are the theory of crime prevention and SWOT analysis, Perkabaharkam Number 1 of 2017 concerning Patrol, the concept of theft, the concept of using communication and information technology, the concept of optimization, concept of patrol, concept of implementation patrol and the concept of the Glympse application. The findings of this study are (1)Implementation of patrols hunting who in their routine activities implement a proactive strategy, routine in nature, patrolling R2 and R4 motorized vehicles in the form of random patrols/random. The hunting patrol consists of the preparation stage, the aap stage, the implementation stage, the termination stage, and the supervision, control, and analysis and evaluation stages; (2)The results of optimizing the patrols of the Sabhara Unit are influenced by supporting and inhibiting factors; (3)In improving optimization, it is carried out by implementing the Park, Walk, Talk patrol method and using the Glympse application for hunting patrol supervision.